Original articleTropical skin diseases imported by travellers returning from Equatorial Africa or Asia - Paul, Małgorzata; Stefaniak, Jerzy; Waśniowski, Aleksander (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
In recent years in Poland, the increasing number of reported tourist and business trips to tropical and subtropical areas is a source of a significant risk of imported exotic infections, including parasitic skin diseases. Skin infections caused by parasites and acquired in hot climate countries are most frequently observed in tourists, missionaries and health workers living in poor sanitary and environmental conditions of a low socioeconomic level, who do not always comply with tropical hygiene measures. Long stay in the endemic zone, frequent exposure to mosquito bites at night, lack of dressing in appropriate clothes with trousers and long sleeves or use of repellents after sunset significantly increase the risk of cutaneous leishmaniosis and lymphatic filariasis. We describe three cases of Wuchereria bancrofti invasion imported by missionaries from Cameroon and India, one case of Leishmania major infection after trekking through Mali and Burkina Faso, and a very rare case of co-existence of bancroftian filariasis and cutaneous leishmaniosis in a nurse who was working for years in a missionary centre in Chad.